1987
DOI: 10.3109/00365528709011152
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Induced Gastric Ulcers in the Rat

Abstract: Low doses of insulin (less than 1.25 IU/kg body weight) stimulate gastric acid secretion in the rat, whereas higher doses (greater than 2.5 IU/kg) release gastrin and cause gastric ulcers but do not increase acid secretion. In this study we have characterized the ulcerogenic properties of insulin in the rat. A dose of 5 IU/kg subcutaneously proved to be maximally effective. Ulcer formation was rapid, and the maximum 90% incidence was reached after 5 h. Both glucose administration and food intake protected agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nevertheless, abnormal clinical signs and body weight changes were not observed in the animals exhibiting testicular changes. With respect to the localized reddish discoloration observed on the stomach, gastric ulcers are known to be caused by insulin administration to fasted rats (Axelson et al, 1987). It should be noted that the testicular changes were observed irrespective of the observed stomach changes.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, abnormal clinical signs and body weight changes were not observed in the animals exhibiting testicular changes. With respect to the localized reddish discoloration observed on the stomach, gastric ulcers are known to be caused by insulin administration to fasted rats (Axelson et al, 1987). It should be noted that the testicular changes were observed irrespective of the observed stomach changes.…”
Section: Discussionmentioning
confidence: 97%
“…In these investigations, the mechanism underlying the increased susceptibility of the gastric mucosa in diabetic animals to damage was multifactorial, and involved increased inflammatory cytokines, decreased gastric blood flow at the ulcer margin, decreased biosynthesis of endogenous prostaglandins in the gastric mucosa, impaired function of heat shock protein (HSP) in the gastric mucosa, and suppression of growth factor production in the gastric mucosa. Furthermore, it has been well known that hyperinsulinemia is associated with type 2 diabetes, it has been demonstrated that over-dose insulin induced gastric ulcer in rats [9,10]. Increased insulin in diabetic animals may be involved with gastric ulcer healing.…”
Section: Introductionmentioning
confidence: 99%